Visible Light Communication: A System Perspective - Overview and Challenges - Rehman, SU; Ullah, S; Chong, PHJ; Yongchareon, S; Komosny, D (MDPI, 2019)
Visible light communication (VLC) is a new paradigm that could revolutionise the future of wireless communication. In VLC, information is transmitted through modulating the visible light spectrum (400–700 nm) that is used for illumination. Analytical and experimental work has shown the potential of VLC to provide high-speed data communication with the added advantage of improved energy efficiency and communication security/privacy. VLC is still in the early phase of research. There are fewer review articles published on this topic mostly addressing the physical layer research. Unlike other reviews, this article gives a system prespective of VLC along with the survey on existing literature and potential challenges toward the implementation and integration of VLC.
Keywords: Visible light communication; Optical communication; LED Communication; VLC networks